TECHNOPRENEURSHIP INTENTIONS IN FACULTY OF COMPUTER SCIENCE BRAWIJAYA UNIVERSITY STUDENTS - Mursityo, Yusi Tyroni; Astuti, Endang Siti; Suharsono, Eko Ganis (Universitas Brawijaya, Indonesia, 2017)
This study investigates whether information technology students participation within factors such as desirability and feasibility affects Creativity and Technopreneurship Intentions before or after their graduation. Using a sample of 187 students within computer science faculty, Brawijaya University, this study finds that participation in desirability and feasibility and Creativity is positively associated with measured Technopreneurship Intentions. Sem-pls analysis methods with SPSS and Warp-PLS is implemented. Further analysis arising from desirability and feasibility reveals that is fully mediated with Creativity and Technopreneurship Intentions. Overall, these findings offer empirical evidence on the importance of desirability and feasibility of the relationship between Creativity and Technopreneurship Intentions.